The effect of self-regulated learning and learning interest on mathematics learning outcomes - Arigiyati, Tri Astuti; Kusumaningrum, Betty; Maysaroh, Irma Leny; Kuncoro, K. S.; Pahmi, Samsul; Özsüt, Bahadır (UNION : Jurnal Ilmiah Pendidikan Matematika, 2023)
Learning outcomes are one of the important aspects in the learning process because it is used as a determining factor for the success of a learning process. The factors that influence student learning outcomes are divided into two, namely internal factors (learning interests, talents, motivation, self-regulation, etc.) and external factors (school environment, family environment, etc.). Self-regulation and learning interest were the focus of discussion in this research. This study aims to determine the positive and significant influence between independence and interest in learning on mathematics learning outcomes for class VIII students of SMP Negeri 24 Muaro Jambi. This type of research is associative quantitative research. The results showed that partially independence had a positive but not significant effect on mathematics learning outcomes with tcount = 1,323 and correlation coefficient 0,202, while interest in learning had a positive and significant effect mathematics learning outcomes with tcount = 4,193 and correlation coefficient 0,548. Simultaneously, independence and interest in learning have a positive and significant effect on mathematics learning outcomes for class VIII students of SMP Negeri 24 Muaro Jambi as shown by the Fcount = 41,196, with an effect of 66,8% and 33,2% influenced by other variables.